Classical trajectories in Coulomb three body systems (1995)
ABSTRACT: computer program for calculating orbits and Poincaré sections in the classical Coulomb three body problem with arbitrary masses and charges in three dimensional space is presented.The regularization procedure necessary to obtain a reliable numerical integration of the equations of motion is sketched. Different configurations of the helium atom and the positronium negative ion (ps-),obtained with the program, are analyzed.